2019
DOI: 10.1113/jp278088
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal triglyceride accumulation is regulated by mineralocorticoid receptor activation under basal and stress conditions

Abstract: Key points Glucocorticoids (GCs) either enhance or reduce obesity in mammals, but limited information exists on the role of corticosteroid receptors in mediating the effect of GCs on lipid metabolism during postnatal development. Mineralocorticoid receptor (MR) activation leads to triglyceride (TG) accumulation post‐feeding, whereas glucocorticoid receptor (GR) activation reduces TG levels. The TG profile was inversely related to the lipoprotein lipase (lpl) transcript abundance, and this gene was downregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…At 15 days post-fertilization (dpf ), cortisol-treated WT larvae had twofold less tert mRNA compared to both WT control and GRKO larvae (figure 1a). Cortisol levels for 15 dpf larvae treated with 5 µg ml −1 of cortisol have been previously reported [25], and the GRKO larvae are hypercortisolemic compared to WT larvae, precluding the need for additional cortisol treatment [25]. These results further confirm that the cortisol-mediated reduction in tert transcript abundance in the WT larvae is under transcriptional control of GR.…”
Section: (A) Tert Transcript Abundancesupporting
confidence: 78%
“…At 15 days post-fertilization (dpf ), cortisol-treated WT larvae had twofold less tert mRNA compared to both WT control and GRKO larvae (figure 1a). Cortisol levels for 15 dpf larvae treated with 5 µg ml −1 of cortisol have been previously reported [25], and the GRKO larvae are hypercortisolemic compared to WT larvae, precluding the need for additional cortisol treatment [25]. These results further confirm that the cortisol-mediated reduction in tert transcript abundance in the WT larvae is under transcriptional control of GR.…”
Section: (A) Tert Transcript Abundancesupporting
confidence: 78%
“…Although MRs are present in the mammalian skeletal muscle and responsive to aldosterone (Chadwick et al 2015), a physiological role for GC-MR activation in skeletal muscle growth is yet to be characterized. A recent study suggested that MR bind to GREs to mediate GR function in mammals (Mifsud & Reul 2016), and we also recently showed that lipid accumulation in zebrafish larvae requires the activation of both GR and MR, supporting a conserved role for corticosteroid receptors (CRs) interactions in energy metabolism (Faught & Vijayan 2019b).…”
Section: Introductionsupporting
confidence: 66%
“…It is generally accepted that cortisol signaling, especially in terms of metabolic regulation, occurs through GR in fish (Mommsen et al 1999, Mommsen 2001. There is evidence that MR is involved in lipid accumulation and adipogenesis in mammals (Marzolla et al 2012), and this was also recently shown in zebrafish (Faught & Vijayan 2019b). Furthermore, activation of MR in human skeletal muscles with the GR agonist prednisolone regulated a suite of genes similar to that seen in response to GR activation by the same agonist (Chadwick et al 2015).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…A similar comparative experimental setting was conceived by Faught & Vijayan (2019b) to study the roles of Gr and Mr, as well as their specific interaction, on lipid metabolism, under basal and stressful conditions (cortisol treatment). In their work, the authors showed that Mr, the only receptor present in Gr mutants, plays a fundamental role in the biosynthesis of triglycerides and in lipid accumulation by downregulating the transcription of the enzyme lipoprotein lipase, thus explaining the increase of adipose tissue previously reported in Gr mutant lines (Facchinello et al 2017, Faught & Vijayan 2019a.…”
Section: Mutants Of Glucocorticoid Receptors In Zebrafishmentioning
confidence: 99%